A Hemimysis Driven Novel Ecosystem at a Modified Boulder Breakwall - (:unkn) unknown (My University, 2017)
The US Army Corps of Engineers (USACE) is mandated to maintain and repair aging breakwall structures in all commercial ports on the Great Lakes. In May of 2014, the construction of Milwaukee Harbor USACE “green” breakwall (GBW) reconciliation created complex rocky aquatic habitat by depositing cobble-sized stone as a veneer over standard 6-10 ton boulders, thus creating “control” (boulder) and “treatment” (cobble) habitats. The breakwall is home to a prolific population of Hemimysis anomala, the introduced Ponto-Caspian mysid, which is significantly more abundant on cobble versus boulders (p
Keywords: Alewife; Ecology; Food Web; Hemimysis; Novel Ecosystem; Rainbow Smelt